Scented traces - Dermal exposure of synthetic musk fragrances in personal care products and environmental input assessment - Vera Homem (2015)
Synthetic musks are organic compounds used as fragrance and fixative additives in several personal care products. Until now, little is known about their occurrence and distribution in these household commodities. However, this information is essential to perform a human dermal exposure assessment. Therefore, this study gives an overview on the levels of 12 synthetic musks in 140 personal care products from 7 different categories (body and hair wash, toilet soaps, shaving products, dentifrice products, deodorants/antiperspirants, moisturizers and perfumes). They were analysed by QuEChERS extraction followed by gas chromatography-mass spectrometry. Detection limits were found between 0.01 ng g-1 (galaxolide) and 5.00 ng g-1 (musk xylene). Higher average concentrations of total synthetic musks were detected in perfumes (5245.05 Îg g-1) and shampoos (487.67 Îg g-1) for adults. Galaxolide, exaltolide and cashmeran were the most detected compounds. Combining these results with the daily usage amounts, an average daily dermal exposure of 75.69 Îg kg-1bw day-1 for adults and 15.54 Îg kg-1bw day-1 for babies/children was achieved. The main contributors for adult and babies/children dermal exposure were perfumes and lotions, respectively. About 40% of the adult daily dermal exposure is related to exaltolide, 30% galaxolide, and 15% tonalide, while for babies/children 96% occurs due to exaltolide. An estimate of the amount of musks discharged "down-the-drain" into the wastewater treatment systems through the use of toiletries was also performed. An average emission per capita of 6.7 mg day-1 was determined and galaxolide and exaltolide were the predominant musks in the effluents. Â(c) 2015 Elsevier Ltd.